2020
DOI: 10.12688/gatesopenres.13133.1
|View full text |Cite
|
Sign up to set email alerts
|

Developing laboratory capacity for Good Laboratory Practice certification: lessons from a Tanzanian insecticide testing facility

Abstract: Background: With increasing insecticide resistance in malaria-endemic countries there is an urgent need for safe and effective novel vector control products. To improve the capacity of facilities that test insecticides in sub-Saharan Africa, a programme is supporting seven facilities towards Good Laboratory Practice (GLP) certification, the globally recognized standard for quality management system (QMS) for the conduct of non-clinical and environmental studies. The World Health Organization (WHO) GLP Handbook… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Begg et al [ 35 ] discussed how computer systems are of particular importance in the process of GLP certification in low- and middle-income countries, even though their role is not always emphasized on accreditation systems around the world. This review identified that the knowledge on laboratory management software is mainly originated, as expected, from developed, high-income countries, with advanced information technology industries and significant investment in technology and support for universities and study centers (USA, Germany, Canada, United Kingdom, Switzerland).…”
Section: Discussionmentioning
confidence: 99%
“…Begg et al [ 35 ] discussed how computer systems are of particular importance in the process of GLP certification in low- and middle-income countries, even though their role is not always emphasized on accreditation systems around the world. This review identified that the knowledge on laboratory management software is mainly originated, as expected, from developed, high-income countries, with advanced information technology industries and significant investment in technology and support for universities and study centers (USA, Germany, Canada, United Kingdom, Switzerland).…”
Section: Discussionmentioning
confidence: 99%
“…For the purpose of this study, the key dimension of variation was role within the test facility, in recognition that this will have determined both which aspects of the GLP certification process individuals were involved with, and the tasks and duties required of them. Sampling included those who hold key roles within a test facility, as determined by a case-study conducted on the first test facility to achieve GLP certification, KCMUCo-PAMVERC 22 , as well as multiple representatives at each organisational level of the facility. This allowed triangulation between different data sources to determine the trustworthiness of findings.…”
Section: Methodsmentioning
confidence: 99%
“…Semi-structured interviews were conducted with individual staff members involved in the GLP process in three test facilities: KCMUCo-PAMVERC, NIMR Amani Centre, and CSRS. The interview topic guide 20 was developed based on previous studies of laboratory capacity strengthening 8 , with additional questions derived from findings from a case study of the GLP certification process at PAMVERC-KCMUCo 22 . One overarching question was specifically related to perceived effects of the project.…”
Section: Methodsmentioning
confidence: 99%
“…Semi-structured interviews were conducted to explore the factors influencing the rate of progress towards sustainable GLP certification at their test facility. The interview topic guide was developed based on previous studies of laboratory capacity strengthening [ 10 ], with additional questions derived from findings from a case study of the GLP certification process at KCMUCo-PAMVERC [ 17 ]. Specific questions asked from the topic guide were matched to the roles and responsibilities of the interviewee.…”
Section: Methodsmentioning
confidence: 99%
“…The KCMUCo-PAMVERC test facility in Moshi, Tanzania was selected as a test case, to establish the feasibility of achieving GLP certification and succeeded in being granted certification in 2017 [ 17 ]. The experience and lessons learnt regarding the process of working towards GLP certification at KCMUCo-PAMVERC were useful subsequently to inform the joint approach by IVCC and the remaining collaborating test facilities.…”
Section: Introductionmentioning
confidence: 99%